Criminal nomads: the role of multiple memberships in the criminal collaboration network between Hells Angels MC and Bandidos MC - Mondani, Hernan (The criminology of Carlo Morselli ; part 2, 2024)
Outlaw motorcycle gangs (OMGs) have received increased attention from both law enforcement agencies and the research community. This study investigates the criminal collaboration patterns of two OMGs with a long history of hostilities. We use government data on individuals registered as belonging to Hells Angels MC, Bandidos MC and individuals with multiple OMG memberships, and suspicion data from 2011 to 2016 to build co-offending networks. Our results show that members of multiple OMGs tend to have higher centrality and clustering. These members also have the highest levels of suspicions per capita, and most of the co-offending is related to nexus links involving multiple membership individuals. They can be described as ‘criminal nomads’, collaborating with individuals from different organisations. Our results suggest that core members tend to engage in white-collar crime to a greater extent than those on the periphery, which tend to engage more in violence and drug crime.